2018
DOI: 10.1371/journal.pone.0199463
|View full text |Cite
|
Sign up to set email alerts
|

Do weather changes influence physical activity level among older adults? – The Generation 100 study

Abstract: IntroductionUnderstanding how individual and environmental factors impact physical activity (PA) level is important when building strategies to improve PA of older adults. No studies have examined how hour-to-hour weather changes influence PA in older adults or how the association between weather and PA eventually is related to cardiorespiratory fitness (CRF) measured as peak oxygen uptake. The aim of this study was therefore to examine how hour-to-hour changes in weather effects hour-to-hour PA in a cohort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 41 publications
(61 reference statements)
3
54
2
3
Order By: Relevance
“…This study showed a positive association between the amount of total PA and temperature in women but not in men. This is in contrast to the study results of Aspvik et al in Norway and Klenk et al in Germany, as they reported statistically significant associations for women and men [9,14]. Other studies found a positive association between PA and temperature as well.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…This study showed a positive association between the amount of total PA and temperature in women but not in men. This is in contrast to the study results of Aspvik et al in Norway and Klenk et al in Germany, as they reported statistically significant associations for women and men [9,14]. Other studies found a positive association between PA and temperature as well.…”
Section: Discussioncontrasting
confidence: 95%
“…The reported negative association of PA and wind in men is in line with the results of Klenk et al Their analyses, however, also indicated a reduction in PA with increasing wind in women [9]. In contrast, Aspvik et al found a statistically significant positive association of PA and wind in women but not in men [14].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, seasons are a crude measure when it comes to understanding the effects of weather on PA [36]. Previous studies have observed the effects of several factors related to the season on daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…Some factors may indirectly influence body weight by their association with variables such as physical activity and diet. For example, extreme temperatures, particulate matter in the air, high precipitation, lower altitude living, urban residency, and poverty have each been associated with lower levels of physical activity [1][2][3][4][5][6]. Different levels of these factors may explain the large amount of variability of obesity that exists in adults across the United States [6].…”
Section: Introductionmentioning
confidence: 99%